Association of Blood Indices Changes with Parvovirus B19 Infection inThalassemia Patients - Olla Raad Raheem; Ansam Dawod Salman; Noor Qasim Rashid; Ali G. Al- Dulimi (Academic Science Journal)
Parvovirus B19 is responsible for several clinical conditions, such as infectious erythematosus, joint inflammation, fetal hydrops, and chronic hemolytic anemia resembling thalassemia syndrome, as well as transient aplastic crises. B19 can be transferred via respiratory secretions, as well as through the use of blood products and blood transfusions . This study aims to demonstrate the effect of Parvovirus B19 infection on some blood indices in Thalassemia patients. Methods: Ninety patients in the Center of Hematological Diseases of Diyala Directorate of Health were tested for anti-parvovirus B19 IgM using the ELISA technique, and then Full parameters of CBC were determined using the Urit 3000 plus automated system. Statistical analysis was done using SPSS Version 29.   The results of the present study showed that the overall positivity rate of the anti-Parvo B19 IgM marker was 28(31.1%) among thalassemia patients. The results of the association of anti-parvo B19 IgM with the parameters of blood indices (Total WBCs, Lymphocytes, Granulocytes, Hemoglobin, RBCs, and Platelets count) found that the mean ± SD of the total WBC count, total lymphocytes count, total granulocytes count, hemoglobin concentration, total RBC count and platelets count in thalassemia patients who were positive for anti-parvo B19 IgM were 13.93 ± 13.08 cells/ cu.mm, 9.24 ± 12.01 cells/ cu.mm, 4.69 ± 2.46 cell/ cu.mm, 7.59 ± 1.30 gm/dl, 2.79 ± 0.54 corpuscle/ cu. Mm and 469.4 ± 284.8 platelet/ cu.mm, respectively. Parvovirus B19 is transmitted by blood transfusions. Patients with persistent anemia and hematologic illnesses like thalassemia may need ongoing blood infusions and may be given red blood cell units that contain Parvovirus B19.